Study of Singlet Oxygen Dynamics on Silicon Polymer Matrix - Jeong-Wook Hwang; Seung-Jin Jung; Il Heo; Hyun-A Son; Jong-Ho Kim; Kang-Kyun Wang; Yong-Rok Kim (Journal of Analytical Methods in Chemistry)
We report a detailed analysis of singlet oxygen generated from the photofunctional polymer film (PFPF) matrix which is the silicone polymer film (PDMS) embedded with a photosensitizer. Activation and deactivation dynamics of singlet oxygen generated from PFPFs were investigated with time-resolved phosphorescence spectroscopy. The singlet oxygen generated from PFPFs was dissipated into three different regions of the polymer matrix; the inside (component A), the surface (component B), and the outside (component C). According to the deactivation dynamics of singlet oxygen in the polymer matrix, the components B and C are expected to be more important for various applications.